Achieving the balance between evidence and simplicity. Issue 4 (29th April 2020) - Beasley, Richard; Braithwaite, Irene; Semprini, Alex; Kearns, Ciléin; Weatherall, Mark; Harrison, Tim; Papi, Alberto; Pavord, Ian D.
We thank B. Lipworth and colleagues for their insightful comments and for raising the important issue of distinguishing between maintenance and reliever budesonide–formoterol use within the anti-inflammatory reliever (AIR) therapy regimen. We agree that such a distinction may be artificial and not be possible in clinical practice. We consider that this is an important conceptual issue but one that may have limited clinical relevance, when prescribing budesonide–formoterol according to a maintenance and reliever therapy regimen in asthma. Indeed it has been shown, from electronic monitoring of inhaler use, that there is such marked variation in medication use when budesonide–formoterol is used as a maintenance and reliever therapy, both long term and prior to severe exacerbations, that such differentiation is both unrealistic and not required in clinical practice [1, 2]. The proposed anti-inflammatory reliever (AIR) therapy algorithm and action plan provides practical guidance for the use of this regimen in clinical practice https://bit.ly/3c0W7EC